Thermal Initiation of Metiyl Methacrylate Polymerization by lron(111) Chelate Complexes l-tris (diethyl dithiocarbamato) iron (111) . 2- Tris (diphenyl dithiocarbamato) Iron (111) (مجلة ديالى للبحوث الانسانية, 2022)
The bulk polymerizations of methylmethacrylate initiated by l--tris (diethyl dithiocarbamato)iron(l 11) .2- Tris (diphenyl dithiocarbamatollront(l 1 1) .has been studied at 80oC in the dark, without inhibition or retardation is observed, and the rate of polymerization is directly proportional to the square root of initiator concentration, the order with respect to the initiator concentration is (0.5),while the order with respect to monomer concentration was found to be close to (1.8) for initiators and this means that the rate of initiation is dependent on monomer concentration.The total activation energy (Et),initiation energy (Ei) and the values of the kinetic parameter ratio Kp / Kt1\2(where Kp & kt  the rate constants of propagation and termination respectively) were determined .